2017
DOI: 10.3856/vol45-issue1-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary chitin on digestive enzyme activity, growth and survival of Macrobrachium tenellum juvenile prawns

Abstract: ABSTRACT. Macrobrachium tenellum is a freshwater prawn native from Mexico to Peru, with potential for cultivation. Currently, it is extensively exploited by local fisheries. To understand its chitin requirements, a formulated diet with chitin added (5, 10 15, 20, and 25%) was given to juveniles for 60 days. Growth, survival, and enzyme activity (trypsin, chymotrypsin, lipase, amylase, and chitinase) were measured every 15 days. Highest final weight and specific growth rate resulted from diets with 20% chitin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…More studies would be needed to determine if there is an effect on the growth rate of M. tenellum or not. Despite the lower final AIW, the AIDGR (T1, 0.054 ± 0.021; T2, 0.061 ± 0.018; T3, 0.057 ± 0.009) was inside the range of previous reports for M. tenellum, 0.007-0.135 g for 60 culture days (Vega-Villasante et al, 2011;De los Santos-Romero et al, 2017), thus, it would be necessa- Table 2. Growth performance of Macrobrachium tenellum cultured at different stocking densities in a recirculating aquaculture system.…”
Section: Parametermentioning
confidence: 62%
See 2 more Smart Citations
“…More studies would be needed to determine if there is an effect on the growth rate of M. tenellum or not. Despite the lower final AIW, the AIDGR (T1, 0.054 ± 0.021; T2, 0.061 ± 0.018; T3, 0.057 ± 0.009) was inside the range of previous reports for M. tenellum, 0.007-0.135 g for 60 culture days (Vega-Villasante et al, 2011;De los Santos-Romero et al, 2017), thus, it would be necessa- Table 2. Growth performance of Macrobrachium tenellum cultured at different stocking densities in a recirculating aquaculture system.…”
Section: Parametermentioning
confidence: 62%
“…The prawns were fed daily with a commercial shrimp diet (40% crude protein, 7% lipid, and 12% moisture; Nutripec Camaronina, Purina, Mexico). The daily feed ratio was determined based on 10% of wet weight and adjusted after each measurement (De los Santos-Romero et al, 2017). Survival was registered daily.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings indicated that dietary CS reduced abdominal fat percentage, saturated fatty acid ( SFA ) concentration, plasma total cholesterol, and high-density lipoprotein cholesterol concentration; increased plasma total monounsaturated fatty acids ( MUFA ); and improved meat quality of broilers ( Razdan and Pettersson, 1994 , Zhou et al., 2009 ). Other studies also observed that feeding CS improved whole-body lipid metabolism in piglets ( Wang et al., 2003 ) and decreased serum cholesterol concentrations in prawns and fish ( Ørjan et al., 2015 , De los Santos Romero et al., 2017 ). Razdan and Pettersson (1994) found that CS decreased plasma lipid concentration in broiler chickens.…”
Section: Introductionmentioning
confidence: 89%
“…Both enzymes prove to be constantly active in all sizes of organisms, acting on triacylglycerols from the diet and also in those that allow it to obtain energy to be used or transferred as reserve material. Notwithstanding, in juveniles of Macrobrachium tenellum, lower values of lipases were registered (below 50 U/mg protein) (De los Santos‐Romero, García‐Guerrero, Vega‐Villasante, Cortés‐Jacinto, & Nolasco‐Soria, ), but in another experimental study this activity reaches an average of 150 U/mg protein (De los Santos Romero, García‐Guerrero, Vega Villasante, & Nolasco Soria, ). In Litopenaeus vannamei digestive lipases are affected by fasting and increase their activity after 24 hr of treatment, which suggests that lipids are used as energy reserves during fasting (Rivera‐Pérez, Navarrete del Toro, & García‐Carreño, ).…”
Section: Discussionmentioning
confidence: 99%